2008
DOI: 10.1111/j.1755-3768.2007.01049.x
|View full text |Cite
|
Sign up to set email alerts
|

Safety, penetration and efficacy of topically applied bevacizumab: evaluation of eyedrops in corneal neovascularization after chemical burn

Abstract: ABSTRACT.Purpose: That vascular endothelial growth factor (VEGF) plays a major role in inflammatory angiogenesis has been well established. This pilot study was designed to evaluate experimental treatment with bevacizumab eyedrops in corneal neovascularization induced by alkali burn. The feasibility of topical administration, corneal cell viability and corneal penetration were investigated in an animal model. Methods: Eighteen chinchilla bastard rabbit corneas injured with 1 m NaOH were divided into three grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 21 publications
2
30
0
1
Order By: Relevance
“…The antiangiogenic effect of BE in rodent systems observed in the present study are supported by other reports, describing measurable effects of this drug in the rodent model, including induction of apoptosis [20] as well as inhibition of angiogenesis [18,[20][21][22][23][24][25][26] inflammatory cell recruitment and cytokine release [27], vascular permeability [28] and wound healing [29]. Habot-Wilner et al [22] showed a clear dose-dependent effect of BE on corneal neovascularization in Wistar rats.…”
Section: Discussionsupporting
confidence: 87%
“…The antiangiogenic effect of BE in rodent systems observed in the present study are supported by other reports, describing measurable effects of this drug in the rodent model, including induction of apoptosis [20] as well as inhibition of angiogenesis [18,[20][21][22][23][24][25][26] inflammatory cell recruitment and cytokine release [27], vascular permeability [28] and wound healing [29]. Habot-Wilner et al [22] showed a clear dose-dependent effect of BE on corneal neovascularization in Wistar rats.…”
Section: Discussionsupporting
confidence: 87%
“…24 This regression was subsequently verified by additional reports from various groups. 25,26 Uy et al have demonstrated improvement in corneal neovascularization as well as patient comfort in their 2 patients with Stevens Johnson syndrome. 27 Kim et al recently treated 10 eyes with topical bevacizumab, and although initial regression of vessels was observed, a 2-month follow-up demonstrated adverse effects such as epithelial breakdown and stromal thinning.…”
Section: Lim Et Almentioning
confidence: 96%
“…Yatoh et al, 159 in 1998, and Cursiefen et al, 160 in 2004, showed that neutralizing VEGF can promote graft survival in the murine model. The majority of experimental studies 76,138,146,[160][161][162][163][164][165][166][167][168][169][170][171][172][173][174] using bevacizumab have shown a statistically significant reduction in the parameters reflecting NV (area/density/length of CNV and so on.). The effect has been the greatest on newly forming vessels rather than established vessels.…”
Section: Nonsteroidal Anti-inflammatory Agentsmentioning
confidence: 99%